1995
DOI: 10.1111/j.1365-2036.1995.tb00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication in a clinical setting: success rates and the effect on the quality of life in peptic ulcer

Abstract: Background: Helicobacter pylori eradication for peptic ulcer has been widely taken up. Evidence for the efficacy of different regimens is often derived from small series in clinical trials but there is little reporting of everyday practice with unselected patients. Freedom from ulcer relapse has been demonstrated, but not whether this equates with clinical success. Methods: We report on a series of 706 patients with H. pylori infection who, between January 1991 and April 1995, received eradication therapy foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Because upper gastrointestinal disorders negatively affect the QoL of patients, the evaluation of QoL in the treatment of peptic ulcers is very important. The validity of the GSRS and other questionnaires for QoL evaluation in upper gastrointestinal disorders and in H. pylori eradication has been documented [10,11,22,23]. It is essential that disease-specific assessment instruments for gastrointestinal disorders (like the GSRS) continue to be evaluated for reliability and validity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Because upper gastrointestinal disorders negatively affect the QoL of patients, the evaluation of QoL in the treatment of peptic ulcers is very important. The validity of the GSRS and other questionnaires for QoL evaluation in upper gastrointestinal disorders and in H. pylori eradication has been documented [10,11,22,23]. It is essential that disease-specific assessment instruments for gastrointestinal disorders (like the GSRS) continue to be evaluated for reliability and validity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the absence of crossresistance among nitroimidazoles and clarithromycin favors this position. With this therapy, some authors [45] have achieved H pylori eradication in 85% of cases, while others have reported success rates of 86% [125] or even 100% [126] . In favor of this strategy is the study by Magaret et al [127] , who studied a group of 48 patients after failure of previous H pylori therapy with a metronidazolecontaining regimen, and randomized them to either lansoprazole, amoxicillin and clarithromycin twice daily for 14 d, which is the logical approach with triple therapy not repeating metronidazole, or to lansoprazole, bismuth, metronidazole and tetracycline for 14 d, which is the quadruple therapy repeating metronidazole.…”
Section: Rbc Tetracycline and Metronidazolementioning
confidence: 99%
“…Furthermore, the absence of cross-resistance among nitroimidazoles and clarithromycin favors this position. With this therapy, some authors [Gisbert et al 1999a] have achieved H. pylori eradication in 85% of cases, while others have reported success rates of 86% [Reilly et al 1995] or even 100% [Lerang et al 1997]. In favor of this strategy is the study by Magaret et al [2001], who studied a group of 48 patients after failure of previous H. pylori therapy with a metronidazole-containing regimen, and randomized them to either lansoprazole, amoxicillin and clarithromycin twice daily for 14 days (i.e.…”
Section: Introductionmentioning
confidence: 99%